2022
DOI: 10.1002/pssa.202100797
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NO2‐Sensing Properties of Cu‐Loaded SnO2 Nanoparticles Synthesized via Precipitation and Impregnation Methods

Abstract: Herein, NO2 noxious gas sensors based on precipitation/impregnation synthesized SnO2 nanoparticles loaded with Cu2O (Cu2O–SnO2) are presented. The particle properties are characterized by nitrogen adsorption, X‐ray spectroscopic, and microscopic analyses. The NO2‐sensing performances in terms of sensor response, response times, selectivity, and stability are optimized by varying Cu contents. The optimal sensing film (1.0 wt%Cu–SnO2) shows a high sensor response of ≈5680–5 ppm of NO2 at a low operating temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…32 On the other hand, the first principle study by Kılıçet al found that it was energetically favorable for Sn interstitials to be formed mutually alongside O vacancies. 32,33 Therefore, it is deduced that the energy band inside the gap is caused by rehybridized Sn 5s−5p of Sn interstitials formed along with the O vacancies. The clear relative O deficiencies observed in the bulk compared to the surfaces again imply surface depletion.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…32 On the other hand, the first principle study by Kılıçet al found that it was energetically favorable for Sn interstitials to be formed mutually alongside O vacancies. 32,33 Therefore, it is deduced that the energy band inside the gap is caused by rehybridized Sn 5s−5p of Sn interstitials formed along with the O vacancies. The clear relative O deficiencies observed in the bulk compared to the surfaces again imply surface depletion.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%